Methylarginine metabolites are associated with attenuated muscle protein synthesis in cancer-associated muscle wasting - Kunz, Hawley E. (J Biol Chem, 2020)
Cancer cachexia is characterized by reductions in peripheral lean muscle mass. Prior studies have primarily focused on increased protein breakdown as the driver of cancer-associated muscle wasting. Therapeutic interventions targeting catabolic pathways have, however, largely failed to preserve muscle mass in cachexia, suggesting that other mechanisms might be involved. In pursuit of novel pathways, we used untargeted metabolomics to search for metabolite signatures that may be linked with muscle atrophy. We injected 7-week–old C57/BL6 mice with LLC1 tumor cells or vehicle. After 21 days, tumor-bearing mice exhibited reduced body and muscle mass and impaired grip strength compared with controls, which was accompanied by lower synthesis rates of mixed muscle protein and the myofibrillar and sarcoplasmic muscle fractions. Reductions in protein synthesis were accompanied by mitochondrial enlargement and reduced coupling efficiency in tumor-bearing mice. To generate mechanistic insights into impaired protein synthesis, we performed untargeted metabolomic analyses of plasma and muscle and found increased concentrations of two methylarginines, asymmetric dimethylarginine (ADMA) and N(G)-monomethyl-l-arginine, in tumor-bearing mice compared with control mice. Compared with healthy controls, human cancer patients were also found to have higher levels of ADMA in the skeletal muscle. Treatment of C2C12 myotubes with ADMA impaired protein synthesis and reduced mitochondrial protein quality. These results suggest that increased levels of ADMA and mitochondrial changes may contribute to impaired muscle protein synthesis in cancer cachexia and could point to novel therapeutic targets by which to mitigate cancer cachexia.